Catadores de sonhos - Peixoto, Bianca Menezes (2010)
The survey, based on the Program of Postgraduate Studies in Social Psychology, aims at understanding the meaning of social inclusion through formal work on the social project initiative of the Cooperative of Selective Garbage Collection of Capela do Socorro (COOPERCAPS) in São Paulo. Using a qualitative research, it was possible to analyze in the speech of the people involved in that project if that initiative represents transformation and integration of those people into society. The starting point for such analysis were their life stories which allowed me to identify the defined categories -- sense of dignity and social transformation and to correlate them with the discourses in order to establish reflection upon the subject. Thus, the purpose of this research is to understand, through the discourse of the subjects involved, if the social initiative of the cooperative represents a movement of both change and structural transformation -- device of social inclusion -- or if it represents a supportive action, therefore just an adjustment in the life trajectory of a given subject. The field work was conducted using the participatory research methodology by means of a discourse analysis of daily conversations and their categorization with the subjects related to the phenomenon and to the social network of the cooperative. The place of data collection was the work environment of the subjects involved -- the cooperative COOPERCAPS -- where I had the opportunity to participate in the production and work environment of all cooperative shifts and sectors. In the survey, I identified the activities and the characteristics of the work and of its relationship network as well as the conditions related to the workers involved. The contribution I bring to the field allows a better understanding of that social initiative as a supposed device of structural change for citizenship integration, therefore better understanding the ways to enhance inclusion initiatives in order to create a more egalitarian society